Manajemen Perbatasan Maritim: Strategi Pengawasan dan Pemeriksaaan Keimigrasian di Perairan Indonesia - Ridwan Arifin; Eva Achjani Zulfa; Margaretha Hanita; Arthur Josias Simon Runturambi (Badan Strategi Kebijakan Hukum, 2024)
Maritime immigration control and inspection at Indonesia's sea borders encounter significant difficulties due to poor coordination and collaboration among border authorities. This study explores the implementation of maritime immigration regulations in Indonesia, highlighting their lack of alignment with international standards, particularly in terms of border immigration management and inter-agency cooperation. The research aims to assess the existing legal framework and procedures for immigration control and inspection at Indonesia's maritime borders. The methodology applies both internal and external policy evaluations, conducted through an analysis of national regulations and interviews with relevant agencies. The findings show discrepancies between national regulations and international standards, along with weak border immigration management and inadequate coordination, leading to inefficiencies in maritime border control and inspection. This study contributes to providing a framework for maritime border management, the aspects of control and inspection at Indonesia's maritime borders, and redefining the phases of immigration control and inspection in these areas.